First evidence for fin whale migration into the Pacific from Antarctic feeding grounds at Elephant Island. Issue 9 (21st September 2022) - Herr, H.; Hickmott, L.; Viquerat, S.; Panigada, S.
Abstract : This study presents the first long-distance tracks of fin whales ( Balaenoptera physalus ) equipped with satellite transmitters off the Antarctic Peninsula. Southern Hemisphere fin whales were severely depleted by twentieth century industrial whaling, yet recently, they have returned to historical feeding grounds off the northern Antarctic Peninsula, forming large aggregations in austral summers. To date, our knowledge only extended to summer behaviour, while information regarding migration routes and the location of breeding and wintering grounds are lacking. During the austral autumn of 2021, we deployed nsatellite transmitters on four fin whales at Elephant Island. Two transmitters stopped working while the animals were still at the feeding grounds, while two continued to transmit during the transition from feeding activity to migration. Both migrating animals left the feeding ground on 15 April 2021, travelling northward into the Pacific and up along the Chilean coast. The most northerly position received before all tags stopped transmitting on 1 May 2021 was at 48°S. These tracks provide initial evidence of seasonal migratory routes and a first indication toward possible locations of winter destinations. This information, even if preliminary, is critical for investigations of population connectivity, population structure and the identification of breeding grounds of Southern Hemisphere fin whales.